2024
DOI: 10.1021/acsapm.3c02944
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-Diffusional-Based Corrosion Protection Mechanisms of Polyaniline-Primed Fluoropolymer Coatings

Mark Rigel R. Ali,
Szeemaine D. Tigno,
Jackson S. Honeyman
et al.

Abstract: In this study, we developed a series of dual-coating systems composed of poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and electrodeposited polyaniline (PANI) as the primary coating and primer, respectively, for stainless steel (SS). Prior to the PVDF-HFP topcoat application, PANI (in either a doped emeraldine salt (ES) or dedoped base (EB) form) was electrodeposited potentiodynamically on either an etched or unetched SS substrate using H 2 C 2 O 4 as the supporting electrolyte. Tape tests showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…However, when both silane pretreatment and top coating with fluoropolymer were employed (i.e., 5PH/PTH/SS mod ), the impedance increased to almost ∼7.2 MΩ cm 2 , indicating a synergistic effect that significantly boosts the corrosion resistance of the coated substrate. In our previous work employing PANI as an electroconductive primer to PVDF–HFP, we achieved a | Z | 0.1 Hz of approximately 1 MΩ cm 2 (coating thickness about 13 μm) . This result is comparable to our current findings, which also reached roughly the same magnitude using PTH as the electroconductive layer.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, when both silane pretreatment and top coating with fluoropolymer were employed (i.e., 5PH/PTH/SS mod ), the impedance increased to almost ∼7.2 MΩ cm 2 , indicating a synergistic effect that significantly boosts the corrosion resistance of the coated substrate. In our previous work employing PANI as an electroconductive primer to PVDF–HFP, we achieved a | Z | 0.1 Hz of approximately 1 MΩ cm 2 (coating thickness about 13 μm) . This result is comparable to our current findings, which also reached roughly the same magnitude using PTH as the electroconductive layer.…”
Section: Resultssupporting
confidence: 90%
“…The chemical composition of a surface also primarily influences its surface energy. ,, For instance, Zisman et al demonstrated that the surface energy decreases with increasing fluorine content in a polymer, following the sequence: CH 2 > CH 3 > CF 2 > CF 3 . , Fluoropolymers exemplify this principle such that the presence of highly polarized and inert C–F bonds promotes material stability and offers a multifaceted defense mechanism against environmental degradation. This attribute renders them invaluable for designing insulating layers that promote ionic permeability and prevent electron transfer between the metal and corrosive medium, thereby averting the oxidation process. Polyvinylidene fluoride (PVDF) and its CF 3 -containing copolymer, PVDF- co -hexafluoropropylene (PVDF–HFP), represent two exemplary fluoropolymers extensively employed in the coating manufacturing industry. Renowned for their exceptional inertness, these polymers offer remarkable corrosion and wear resistance, alongside mechanical integrity, film-forming characteristics, low surface energy, and thermal stability. , The synergy between PVDF’s durability and chemical resistance and HFP’s inclusion promoting ease of processability yields coatings that boast mechanical flexibility, outstanding protective properties, and lower surface energy. , Despite their inherently low surface energy, these fluoropolymers alone cannot achieve superhydrophobicity. , Customizing rough surfaces using materials with low surface energy or generating a rough surface on hydrophobic materials is typically employed to achieve superhydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…When external potential changes or the material faces corrosion attacks, the stored charges can quickly move to the area that needs protection, forming an electrochemical protective layer that effectively blocks the invasion of corrosive media. This protective layer can not only buffer the attack of corrosive media but also suppress the progress of corrosion reactions by regulating the potential of the metal surface, thus forming effective protection for the metal substrate. Chen et al successfully synthesized pentadecafluorooctanoic acid/polyaniline (PFOA/PANI) composite, creating hydrophobic coatings and improving the anticorrosion performance of epoxy resins. Dong et al successfully synthesized PANI with microcapsule structures and loaded MBT as a corrosion inhibitor, providing dual corrosion protection for carbon steel.…”
Section: Introductionmentioning
confidence: 99%